2011
DOI: 10.4103/0974-7788.83186
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antioxidant potential of Amalakayas Rasayana: A polyherbal Ayurvedic formulation

Abstract: Amalakayas Rasayana (AR) is a polyherbal formulation mentioned in Ayurveda to treat aging and age-associated diseases. Being an antiaging drug, AR may have antioxidants and free radical scavenging activity to minimize free radical-induced damage which is a key cause of aging. The methanolic extract of AR was evaluated in vitro for total phenolic and tannin content, free radical scavenging activity, superoxide radical scavenging activity, and reducing power. The total phenolic content was measured using Folin-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 18 publications
2
9
0
Order By: Relevance
“…Moreover, using an arthritic rat model, Ratheesh et al [31] also found that the Ayurvedic formulation Kerabala increased antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), and decreased the lipid peroxidation product. Another Ayurvedic formulation, Amalakayas Rasayana, also showed antioxidant activity by scavenging activity free radicals [32]. Mathew et al [33] analyzed antioxidant activity of many Ayurvedic plant extracts and found all extracts had positive DPPH (2,2-diphenyl-1picryl-hydrazyl-hydrate) free radical scavenging activity.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, using an arthritic rat model, Ratheesh et al [31] also found that the Ayurvedic formulation Kerabala increased antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), and decreased the lipid peroxidation product. Another Ayurvedic formulation, Amalakayas Rasayana, also showed antioxidant activity by scavenging activity free radicals [32]. Mathew et al [33] analyzed antioxidant activity of many Ayurvedic plant extracts and found all extracts had positive DPPH (2,2-diphenyl-1picryl-hydrazyl-hydrate) free radical scavenging activity.…”
Section: Introductionmentioning
confidence: 99%
“…p-Cresol (1) and cinnamic acid (2) were condensed in the presence of con. H 2 SO 4 under nitrogen atmosphere at 120°C for a period of 6 h to afford 3,4-dihydro-6-methyl-4-phenyl-2H-benzopyran-2-one (3).…”
Section: Resultsmentioning
confidence: 99%
“…These ROS species induce oxidative stress and are also responsible for diabetes, cardiovascular, and many of today's diseases [1][2][3]. They play key role in DNA damage [4], mutations, cellular injury, oncogenesis, and aging process [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are several anecdotal claims which remain to be comprehensively tested through contemporary knowledge. The fruit extracts have been reported to possess antioxidant 5 (Samarakoon et al, 2011), immunomodulatory (Madhuri et al, 2011), anti-helminthic (Dwivedi et al, 2011), antimicrobial (Mehrotra et al, 2010;Saeed and Tariq, 2007), chondro-protective (Sumantran et al, 2008), anti-inflammatory (Sharma et al, 2003), antitumor (Jose et al, 2001) and memory enhancing (Ashwlayan and Singh, 2011) activities. It is also reported to be useful in the lowering of cholesterol, neutralizing snake venom and ophthalmic disorders (Khan, 2009).…”
Section: Described In Indian Traditionalmentioning
confidence: 96%